'If I knew what was going to happen, it wouldn't worry me so much': Children's, parents' and health professionals' perspectives on information for children undergoing a procedure. (December 2019) - Bray, Lucy; Appleton, Victoria; Sharpe, Ashley
Children undergoing procedures such as blood tests and X-rays experience less anxiety and upset if they are well prepared and informed. Currently the provision of information about procedures can be ad hoc and there are barriers to children understanding this information. This study explored the perspectives of 32 children undergoing procedures (aged between 8 and 12 years), 27 parents and 19 health professionals on the provision of preparatory information to children. Qualitative interviews, prompted by visual images, were thematically analysed. The three themes, 'accessing information', 'understanding information' and 'using information', resonated with the central tenets of health literacy. Children reported mainly accessing information second-hand through their parents and demonstrated misconceptions about their procedure. Children identified that procedural information would help them to know what was going to happen and enable them to feel less worried and scared about their procedure. This study highlights that children can have low levels of health literacy in relation to a planned procedure. Their health literacy in this context is heavily influenced by the adults (parents and health professionals) around them. There needs to be further work conducted, informed directly by children, to improve the health literacy of children attending hospital for planned procedures.